Twenty years’ experience in the management of childhood germ cell tumors - TRUE, ÖMER; TOKUÇ, AYŞE GÜLNUR; EKER, NURŞAH (My University, 2017)
Background/Objectives: Germ cell tumors (GCT) account for 2-3% of childhood tumors. It is most commonly seen under 3 years and over 12 years old. GCTs are most commonly localized in the gonads. We have examined our patients who diagnosed and treated with GCT at our center retrospectively. Design/Methods: Sixty two children and adolescence who were diagnosed and treated with GCT at our center between 1996 and 2016 analyzed retrospectively. Results: The patients age ranged between 5 days to 17 years. Thirty-five of patients were girls (57%) and 27 were boys (43%). The most common tumor localization with 29(47%) patients was gonads. Sixteen patients (25,8%) had metastatic disease at presentation. The most common histologic subtype was mature teratoma with 14 (22%) patients and 14 patients (22%) with yolk sac tumor. Alpha-fetoprotein (AFP) was elevated in 29 (46%) of cases whereas beta-human chorionic gonadotropin (-hCG) was elevated in only 4 (4%) of cases. Twenty-two cases (35%) were treated with total surgical resection and they didn't receive chemotherapy. Six patients (10%) received radiotherapy in addition to surgery and chemotherapy. Thirty-three patients (53,3 %) received BEP (bleomycin, etoposide, cisplatin) as a first line chemotherapy. During the follow up 6 (10 %) patients had relapsed. Five years overall survival rate of our patients was 95%, retrospectively. Conclusions: Germ cell tumors have favorable outcome in children. These tumors can be cured with surgical resection followed by cisplatin-based chemotherapy and radiotherapy for selected patients. As a result of our own data analysis, it has been found that our survival rates are similar to current literature data.